2022
DOI: 10.3389/fonc.2022.1010726
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of lenvatinib versus sorafenib in first-line treatment of advanced hepatocellular carcinoma: A meta-analysis

Abstract: ObjectiveLenvatinib and sorafenib are first-line oral multikinase inhibitors approved for the treatment of advanced hepatocellular carcinoma (HCC). However, the choice of the primary therapeutic agent among these two remains controversial. This meta-analysis aimed to estimate the efficacy and safety of lenvatinib and sorafenib in patients with advanced HCC.MethodsPubMed, Cochrane Library, Web of Science, and Embase databases were searched for relevant research published up to June 30, 2022. After quality asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…[31][32][33][34] lenvatinib is a TKI that can replace sorafenib in the first-line treatment of HCC. [35] In contrast to Sorafenib, it is characterized by its strong activity against fibroblast growth factor receptors, [36] and recent studies have shown that it also has immunomodulatory activity. [37] In 2018, the REFLECT trial [38] demonstrated that lenvatinib was superior to sorafenib in improving ORR and prolonging PFS.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33][34] lenvatinib is a TKI that can replace sorafenib in the first-line treatment of HCC. [35] In contrast to Sorafenib, it is characterized by its strong activity against fibroblast growth factor receptors, [36] and recent studies have shown that it also has immunomodulatory activity. [37] In 2018, the REFLECT trial [38] demonstrated that lenvatinib was superior to sorafenib in improving ORR and prolonging PFS.…”
Section: Discussionmentioning
confidence: 99%
“…However, the current landscape has been significantly altered by the introduction of lenvatinib, a multitargeted tyrosine kinase inhibitor [ 109 , 110 ]. As a novel first-line treatment option for HCC, lenvatinib has demonstrated non-inferior overall survival, improved progression-free survival, a higher response rate, and a better disease control rate compared to sorafenib in multiple clinical trials [ 111 , 112 ].…”
Section: Drug Resistancementioning
confidence: 99%
“…5 Despite the excellent clinical results of LEN, it still has some adverse effects. 6,7 Some patients experienced adverse effects such as hypertension and arterial thromboembolism with LEN. 8 In phase III clinical studies of patients with HCC treated with LEN, the incidence of adverse reactions with LEN was 99% in all cases, 3 leaving only the option of reducing the frequency of dosing or changing to another drug.…”
Section: Introductionmentioning
confidence: 99%
“…12 Fe 3 O 4 nano-particles modified by polyethylene glycol (PEG) can increase the water solubility and biocompatibility of drug-loaded materials, avoid the recognition of reticuloendothelial system, prolong the circulation time of drug-loaded materials in vivo, etc. 7 Fe 3 O 4 nano-particles can be metabolized in vivo, and the material itself can be used to treat anemia, such as the “Feraheme” drug, which can be applied in vivo. 13,14 Studies have shown that when magnetic nano-materials are used as contrast agents for MRI, they can form multifunctional drug delivery and imaging systems, and take advantage of the special microenvironment of tumor tissues to design and prepare “smart” nano-drug release systems to improve the therapeutic and imaging effects at the lesion site.…”
Section: Introductionmentioning
confidence: 99%